Genomic characteristics and molecular epidemiology of MRSA from medical centers in Mexico: Results from the Invifar network - Gabriela Echaniz-Avilés; Luis Ángel Núñez-García; Eduardo Rodríguez-Noriega; Consuelo Velázquez-Acosta; Luis Esaú López-Jácome; Eduardo López-Gutiérrez; Talia Pérez-Vicelis; Cristina Torres-Báez; Ulises Garza-Ramos; Nadia Rodríguez-Medina; Juan Manuel Barajas-Magallón; Rosario Vázquez-Larios; et al. (PLoS ONE, 2025)
Introduction The methicillin-resistant Staphylococcus aureus (MRSA) genome varies by geographical location. This study aims to determine the genomic characteristics of MRSA using whole-genome sequencing (WGS) data from medical centers in Mexico and to explore the associations between antimicrobial resistance genes and virulence factors. Methods This study included 27 clinical isolates collected from sterile sites at eight centers in Mexico in 2022 and 2023. Antibiotic susceptibility testing was performed using VITEK 2. In addition, WGS was performed using a NovaSeq platform, and a bioinformatic analysis was conducted using several tools. Results In this study, 21 strains were CC5, five were CC8, and one was CC93. Moreover, six strains were identified as ST5(CC5)-MRSA-IIa- t895, four strains were found to be ST1011(CC5)-MRSA-IIa-t895, five strains were found to be ST1011(CC5)-MRSA-IIa-t9364, one strain was found to be ST1011(CC5)-MRSA-IIa-t8116, another was found to be ST1011(CC5)-MRSA-IIa-t62, three were found to be ST8(CC8)-MRSA-IVa-t8, one strain was ST5(CC5)-MRSA-IVa-t2, one strain was as ST93(CC93)-MRSA-IVa-t3949, two strains were ST9003(CC8)-MRSA-IVa-t18492, and three strains were ST9034(CC5)-MRSA-V-t2. All SCCmec IIa strains showed resistance to levofloxacin and ciprofloxacin, and all but two strains were resistant to clindamycin. Among the strains that harbored the type IIa cassette, most had the aadD, blaZ, and ermA_SDS genes and the erm A gene. Multiple genes for adhesion, enzymes, immune evasion, and secretion system were detected, regardless of SCCmec type. Of the SCCmec IVa strains, most harbored the Panton-Valentine leukocidin encoding genes. Conclusion In this study, the most frequently detected CC was CC5, followed by CC8, and CC93, and the most frequently detected MRSA ST was ST1011, followed by ST5. Most SCCmec elements were found to be type IIa, followed by type IVa. High MIC values were observed for ciprofloxacin, erythromycin, and clindamycin, particularly within SCCmec IIa. Of the SCCmec IVa strains, most harbored the lukS-PV and lukF-PV genes.